Integrating Pancasila Values Through Extracurricular Activities: Character Development in an Indonesian Muhammadiyah Islamic Boarding School - Pewangi, Mawardi; Afandi, Afandi; Hanif, Ahmad; Jarong, Koree (Institut Agama Islam Negeri (IAIN) Manado, 2024)
Character education in Indonesian Islamic boarding schools faces the challenge of integrating national values with religious teachings. This study examines the implementation of extracurricular activities at Muhammadiyah Darul Arqam Gombara Islamic Boarding School in strengthening the Pancasila Student Profile, particularly through an integrated approach combining Islamic values and national character development. Using a qualitative case study design, this research collected data through in-depth interviews with 15 participants, participatory observations of extracurricular activities, and document analysis over six months. The findings reveal that the integration of various extracurricular programs - including arts, sports, Hizbul Wathan scouts, Tapak Suci martial arts, and the Muhammadiyah Student Association - significantly contributes to character development in five key areas: discipline, independence, social skills, moral values, and academic-nonacademic balance. The study highlights how these activities serve as effective platforms for practicing Pancasila values through experiential learning. However, challenges remain in terms of facility limitations, time management, and mentor training. The research concludes that structured extracurricular activities in Islamic boarding schools can effectively support character education when designed holistically, integrating both religious and national values. This model offers valuable insights for other Islamic educational institutions seeking to strengthen character education through extracurricular programs.